Intranuclear filaments containing a nuclear pore complex protein (The Rockefeller University Press, 1993)
Nuclear pore complexes (NPCs) are anchoring sites of intranuclear filaments of 3-6 nm diameter that are coaxially arranged on the perimeter of a cylinder and project into the nuclear interior for lengths varying in different kinds of cells. Using a specific monoclonal antibody we have found that a polypeptide of approximately 190 kD on SDS-PAGE, which appears to be identical to the recently described NPC protein "nup 153," is a general constituent of these intranuclear NPC-attached filaments in different types of cells from diverse species, including amphibian oocytes where these filaments are abundant and can be relatively long. We have further observed that during mitosis this filament protein transiently disassembles, resulting in a distinct soluble molecular entity of approximately 12.5 S, and then disperses over most of the cytoplasm. Similarly, the amphibian oocyte protein appears in a soluble form of approximately 16 S during meiotic metaphase and can be immunoprecipitated from egg cytoplasmic supernatants. We conclude that this NPC protein can assemble into a filamentous form at considerable distance from the nuclear envelope and discuss possible functions of these NPC-attached filaments, from a role as guidance structure involved in nucleocytoplasmic transport to a form of excess storage of NPC proteins in oocytes.